Empowerment Of Waqf For Sustainable Social-Economic Development: A Systematic Literature Review - Ikhsanudin Ikhsanudin; Nursaman Nursaman; Muhamad Fakhrudin (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2026)
ABSTRACT Waqf empowerment is an important instrument in the Islamic economic system with significant potential to enhance social and economic welfare, yet its utilization remains suboptimal. This study aims to systematically analyze the development, patterns, and challenges of waqf empowerment through a Systematic Literature Review approach. The methodology employed is SLR using the PRISMA framework, with data sources derived from scientific articles published between 2022 and 2026 and selected based on predefined inclusion and exclusion criteria. The results indicate that productive waqf, cash waqf, and integration with zakat and Islamic social finance are key strategies in empowering the economy. The discussion highlights that innovation in management, the role of community-based institutions such as Islamic boarding schools, and support from policy and digitalization are crucial factors in enhancing waqf effectiveness. Furthermore, the study identifies challenges including low waqf literacy, limited managerial capacity, and suboptimal asset utilization. In conclusion, waqf empowerment has strong potential as a sustainable development instrument if managed professionally, innovatively, and in an integrated manner. Keyword: cash waqf, productive waqf, sustainable development, systematic literature review, waqf empowerment